Investigational agents in metastatic basal cell carcinoma: focus on vismodegib - Batty N; Kossoff E; Dy GK (Dove Medical Press, 2012)
Nicolas Batty,1 Ellen Kossoff,2 Grace K Dy11Department of Medicine, Roswell Park Cancer Center, Buffalo, NY, USA; 2Department of Pharmacy, Roswell Park Cancer Center, Buffalo, NY, USAAbstract: Vismodegib (GDC-0449, 2-chloro-N-(4-chloro-3-(pyridin-2-yl)phenyl)-4-(methylsulfonyl)benzamide, Erivedge™) is a novel first-in-human, first-in class, orally bioavailable Hedgehog pathway signaling inhibitor of the G-protein coupled receptor-like protein smoothened (SMO) which was approved in the United States on January 2012. This signaling pathway is involved in the carcinogenesis of several types of tumor, as exemplified by basal cell carcinoma. This review focuses on the role of the Hedgehog pathway in the pathogenesis of basal cell carcinoma, the pharmacology and the clinical activity of vismodegib, as well as a brief summary of investigational agents in development targeting this pathway.Keywords: hedgehog inhibitors, metastatic basal cell carcinoma, hedgehog signalling pathway